2010
DOI: 10.1002/prca.201090107
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of synaptosomal protein expression reveals that cerebral ischemia alters lysosomal Psap processing

Abstract: The aim of the present study was to determine whether combined administration of monoclonal antibody (Herceptin ® , trastuzumab) and anti-HER-2 (clone CB11) with hyaluronic acid (HA) and lipoplex (containing lipofectamine (LipA) and plasmid DNA) can produce a synergistic reaction to increase the therapeutic effect of monoclonal antibodies. To assess the treatment response, we cultured a 3-D MCF-7 cell line overexpressing HER-2 and CD44 receptors. The high density 3-D cell aggregation in the hollow fiber biorea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 9 publications
3
8
0
Order By: Relevance
“…7B). Consistent with our previous report (Costain et al 2010), approximately half (51%) of the IS dataset were mitochondrial proteins (Fig. 7B), whereas < 25% of known synaptosomal proteins are mitochondrial.…”
Section: Label-free Proteomic Analysis Of Ischemic Synaptosomessupporting
confidence: 79%
See 4 more Smart Citations
“…7B). Consistent with our previous report (Costain et al 2010), approximately half (51%) of the IS dataset were mitochondrial proteins (Fig. 7B), whereas < 25% of known synaptosomal proteins are mitochondrial.…”
Section: Label-free Proteomic Analysis Of Ischemic Synaptosomessupporting
confidence: 79%
“…6). Consistent with our previous study, the majority of the IS proteins were localized in the mitochondria (Costain et al 2010), and the localization of the remaining proteins was consistent with the synaptic compartment. Furthermore, literature mining of PubMed indicated that only ≈ 15% of the IS proteins were associated with the MCAO model of cerebral ischemia.…”
Section: Cerebral Ischemia-induced Alterations In the Synaptic Proteomesupporting
confidence: 78%
See 3 more Smart Citations